DAMPAK PANDEMI COVID - 19 TERHADAP PEREKONOMIAN SERTA PEMBANGUNAN DI PEDESAAN - ESKI ADITYA; SYFA ARIKAH; NURUL JANNAH (LP2MTBM MAKARIOZ, 2022)
This study aims to examine the impact of Covid-19 on the people's economy and village development. Villages alwaysreceive assistance, leading to or causing the village to lose its identity. The loss of village identity is proven by the existenceof whatever is required by the government in its transmission, it must get an imbalance in the form of material. the basicproblem of how to meet basic human needs in order to carry out activities in the world in order to meet welfare, safety. thecorrelation between village democracy and the direction of the economy and village development which is an inseparableunit. Democracy affects the response to Covid-19, is a real result of village democracy in realizing the economy anddevelopment. Research to determine the impact of the endemic on the village economy, village development which is beinghit globally. The views of the village community have experienced a crisis of trust, as a result of the role of the central andregional governments that pay less attention to the village as an independent government, losing its identity. For the sake ofrealizing a village democracy in the field of economy and development, ideally it forms the character of citizens who are freefrom dependence.